Salud y bienestar con el Chi Kung - Pan González, Juan (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: FR; mso-bidi-font-weight: bold;" lang="FR">Marc Boillat de Cogemont Sartorio. Barcelona: Alas, 2002. 144 páginas. 24x17 cm. I.S.B.N.: 84-2030-427-1.